Pemberdayaan Perempuan Anggota Nasyiatul Aisyiyah Kota Sukabumi melalui Pelatihan Penulisan Kreatif - Setiadi, David; Humaira, Hera Wahdah; Firdaus, Asep (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
This community service activity focuses on empowering women who are members of the Nasyiatul Aisyiyah organization in Sukabumi City. The activity involves creative literary writing, specifically focusing on poetry. This creative writing training for Nasyiatul Aisyiyah members will be beneficial for empowering women to be able to utilize literary and journalistic media in channeling their creative ideas. In addition, this activity is an alternative in supporting the flagship programs of the Nasyiatul Aisyiyah Central Leadership, such as women's empowerment in the field of women's leadership, digital literacy, and the Muhammadiyah Young Women's Symposium. Through this activity, several creative works in poetry writing were produced by women who are members of the Nasyiatul Aisyiyah organization in Sukabumi City.